Validación de un instrumento de registros de enfermería en periodo preoperatorio, transoperatorio y postoperatorio - Lizalde Hernandez, Azucena (Universidad Michoacana de San Nicolás de Hidalgo, 2008)
To validate a registration nursing format for the preoperative, intraoperative and postoperative phases. Methodology: The investigation was descriptive, transversal, prospective, with a sample non probabilistic by convenience of 27 subjects from the three shifts, which create a group of nurses that recorded the nursing care given during the perioperative phase in the new clinical registration sheet. The instrument (Nursing Clinical Record Sheet) was designed and 27 nurses were capacitated, who signed the informed consent, explaining to them the instrument’s structure according to the filling instructive. Validation of construct: Sustained by Betty Neuman’s theoretical model, stressing factors were identified; it was specified and established the theoretical relation between concepts. Validation of content: Establishing the anxiety diagnostic, according to NANDA, NIC and NOC, implemented during the perioperative phase; within the work group nine nurses were selected at random, three from each shift and from these one for every phase, with the criteria of every nurse, from the most labor inexperienced recently graduates to the most experienced, knowing and skilled, could apply the instrument equally. Validation of criteria: Selecting another nine nurses in the same fashion that before, they carried on the record on the instrument applied to programmed patients for surgery treatment; during the preoperative phase the instrument was applied to laparatomy, craniotomy and mammal nodule resection, during the intraoperative phase to patients being intervened for a caesarean section, a femur fracture reduction, and an open appendectomy, during the postoperative phase to patients from a kidney transplant, a coloecystectomy , laparoscopy and a rhinoplasty.

Validar un formato de registros de enfermería durante el periodo preoperatorio, transoperatorio y postoperatorio. Metodología fue una investigación, descriptiva, transversal, prospectiva, con muestra no probabilística por conveniencia de 27 sujetos, de los tres turnos, formando un grupo de enfermeras que proporcionaron y registraron cuidados en la nueva hoja de registros clínicos, durante el peri operatorio. Se diseñó el instrumento Capacitando a (hoja de registros de enfermería). 27 enfermeras, que firmaron el consentimiento informado, explicándoles la estructura del instrumento, de acuerdo al instructivo de llenado. La Validación: De Constructo. Sustentado en el modelo teórico de Betty Neuman, identificando factores estresantes, se estableció y especifico la relación teórica entre los conceptos. Validación de contenido, estableciendo el diagnostico de ansiedad, según la NANDA, NIC y NOC, se implementó durante el peri operatorio; dentro del grupo de trabajo se seleccionaron 9 enfermeras al azar, tres de cada turno y de estas una en cada periodo, con el criterio que toda enfermera recién egresada, con menos experiencia laboral, y la más experta con mayores conocimientos y habilidades, pudieran aplicar el instrumento. Validación de criterio. Seleccionando otras 9 enfermeras de igual forma que las anteriores, realizaron el registro en el instrumento aplicado a pacientes programados para tratamiento quirúrgico, durante el preoperatorio el instrumento se aplicó en pacientes para laparotomía, craneotomía y resección de nódulo mamario. En el transoperatorio, a pacientes que estaban siendo intervenidos de cesárea, reducción de fractura de fémur y apendicetomía abierta. En el posoperatorio a pacientes de trasplante renal, colecistectomía laparoscopia y rinoplastia.
Facultad de Enfermería. Maestría en Enfermería
Keywords: info:eu-repo/classification/cti/3; FE-M-2008-0010; Preoperatorio; Transoperatorio; Posoperatorio; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5618